The applications of buckminsterfullerene C60 and derivatives in orthopaedic research. (April 2014) - Liu, Qihai; Cui, Quanjun; Li, Xudong Joshua; Jin, Li
Abstract Buckminsterfullerene C60 and derivatives have been extensively explored in biomedical research due to their unique structure and unparalleled physicochemical properties. C60 is characterized as a "free radical sponge" with an anti-oxidant efficacy several hundred-fold higher than conventional anti-oxidants. Also, the C60 core has a strong electron-attracting ability and numerous functional compounds with widely different properties can be added to this fullerene cage. This review focused on the applications of C60 and derivatives in orthopaedic research, such as the treatment of cartilage degeneration, bone destruction, intervertebral disc degeneration (IVDD), vertebral bone marrow disorder, radiculopathy, etc., as well as their toxicity in vitro and in vivo. We suggest that C60 and derivatives, especially the C60 cores coupled with functional groups presenting new biological and pharmacological activities, are advantageous in orthopaedic research and will be promising in clinical performance for musculoskeletal disorders treatment; however, the pharmacokinetics and toxicology of these agents as local/systemic administration need to be carefully determined.